FINANCING MANAGEMENT ANALYSIS OF PASIR KOPO DAM CONSTRUCTION PROJECT IN BANTEN PROVINCE - Napitupulu, Reynaldo Vernandes Matheus; Rarasati, Ayomi Dita (Universitas Ibn Khaldun Bogor, 2022)
The strategic program of the Republic of Indonesia's Government is stated in the National Medium-Term Development Plan (RPJMN) for 2020 – 2024.One of its targetisconstruction of eighteen (18) multipurpose dams. Pasir Kopo Dam is included in the RPJMN target and its expected to provide raw water supply, irrigation water, and increase the potential for electrical energy through Micro-Hydro Power Plant (PLTMH). However, the dam construction requires a huge project costs which can't be handled solely by State Budget (APBN). There is funding gap in State Budget for financing the dam construction, so another financing alternative is needed. Public Private Partnership (PPP)is an alternative financing scheme for dam construction. PPP is influenced by economic feasibility analysis and identification of influential project risks. The selection of an investment-worthy PPP Scheme in the Pasir Kopo Dam Development Project is expected to be mutually beneficial for all parties involved in the cooperation.